Metataxonomic profiling of microbial communities and metabolic analyses of the traditional Spanish raw cow’s milk cheese ‘Casín’ from manufacture to ripening - Rodríguez, Javier; Suárez, Paula R.; Vázquez, Lucía; Flórez, Ana Belén; Vivar-Quintana, Ana María; Mayo, Baltasar (Frontiers in Microbiology, 2025)
‘Casín’ is a soft, rindless, strongly flavored, Spanish PDO cheese made from raw cow’s milk, the production of which involves a distinctive kneading process during ripening. This study aimed to characterize the bacterial and fungal communities developing during Casín cheese manufacture and ripening, assess their metabolic activity on milk components, and explore correlations between microbial dynamics and physicochemical and volatile organic compounds (VOC) profiles. Bacterial and fungal populations were assessed by culturing and high-throughput amplification and sequencing of 16S rRNA gene and ITS ribosomal regions, while basic tests and high-resolution chromatography techniques were employed to assess physico-chemical parameters and metabolite profiles. Metataxonomic analyses revealed a rich microbial diversity during Casín cheese manufacture and ripening, with a progressive decline in diversity as maturation advanced. Thirty-two bacterial and 30 fungal phylotypes were detected at relative abundances >0.5% in at least one sample. Lactococcus lactis/L. cremoris and Geotrichum candidum consistently dominated bacterial and fungal communities, respectively, across all batches and time points. Concentrations of lactic and butyric acids increased throughout ripening, reflecting active fermentation and lipolysis. Among the VOC, hexanoic, butanoic, octanoic, and n-decanoic acids were the most abundant, with total VOC levels rising steadily and peaking at day 60. These compounds likely contributed to the strong characteristic aroma of mature Casín cheese. Co-occurrence and co-exclusion network analyses, combined with correlations between microbial and metabolic data, suggested that specific microorganisms play central roles in developing the distinctive sensory characteristics of Casín cheese. The results highlight the pivotal contribution of the microorganisms to the biochemical transformations underlying Casín cheese ripening. Dominant taxa, supplemented or not with subdominant taxa, have the potential to serve as the basis for developing a defined complex starter culture, aiming at maintaining the sensory distinctiveness of this PDO cheese, while improving process consistency and microbial safety.